2020
DOI: 10.1177/0957650920946533
|View full text |Cite
|
Sign up to set email alerts
|

Velocity characteristics in a multiphase pump under different tip clearances

Abstract: To investigate the effect of tip clearance on the velocity distribution in a multiphase pump, the internal flow and velocity distribution characteristics in pump under different tip clearances are studied using experimental and numerical methods. Simulations based on the Reynolds-Averaged Navier-Stokes equations (RANS) and the standard k-ε turbulence model are carried out using ANSYS CFX. Under conditions of inlet gas void fraction (IGVF) is 5% at the flow rate of 0.6Q, 0.7Q and 0.8Q (Q is the design flow rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…Over the past few decades, numerous academic studies have been conducted to assess flow loss. [12][13][14] Yasuyuki et al 15 proposed a method for the quantitative analysis of hydraulic loss through a combination of numerical simulations and model tests, and they analysed the hydraulic loss of different flow-passing components in the turbine. However, as the internal flow of hydraulic machinery exhibits complex threedimensional motion, the flow loss exhibits an uneven distribution in space.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, numerous academic studies have been conducted to assess flow loss. [12][13][14] Yasuyuki et al 15 proposed a method for the quantitative analysis of hydraulic loss through a combination of numerical simulations and model tests, and they analysed the hydraulic loss of different flow-passing components in the turbine. However, as the internal flow of hydraulic machinery exhibits complex threedimensional motion, the flow loss exhibits an uneven distribution in space.…”
Section: Introductionmentioning
confidence: 99%
“…Kim Changhyun et al [8] proposed four different sizes of inducer tip clearances, and hydraulic performance under cavitation condition and non-cavitation condition was analyzed by simulation. Shi Guangtai et al [9] analyzed the internal flow and velocity distribution characteristics of the multiphase pump under different tip clearances, by employing the high-speed photography and numerical simulation, it found that tip leakage vortex has significant effect on the tip separated vortex and the hydraulic loss of pump. Li Wei et al [10][11] proposed a mixed-flow pump model with non-uniform tip clearance, through the technology of particle image velocimetry to analyze the effect of flow rate and eccentricity on the flow characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the BTC of the traditional pump is similar to the backflow clearance of full tubular pump, and the research on BTC can provide some references. Many scholars used numerical simulation and test measurement (high-speed photography and particle image velocimetry) to study the TLV in axial flow pump [7], mixed flow pump [8], pump jet [9,10], and multiphase pump [11]. The research found that the evolution of TLV includes splitting stage, developing stage and merging stage [12].…”
Section: Introductionmentioning
confidence: 99%